2006
DOI: 10.1182/blood-2006-06-027409
|View full text |Cite
|
Sign up to set email alerts
|

Only the CD45RA+ subpopulation of CD4+CD25high T cells gives rise to homogeneous regulatory T-cell lines upon in vitro expansion

Abstract: Thymus-derived CD4 ؉ CD25 ؉ regulatory T cells suppress autoreactive CD4 ؉ and CD8 ؉ T cells and thereby protect from autoimmunity. In animal models, adoptive transfer of CD4 ؉ CD25 ؉ regulatory T cells has been shown to prevent and even cure autoimmune diseases as well as pathogenic alloresponses after solid organ and stem-cell transplantations. We recently described methods for the efficient in vitro expansion of human regulatory T cells for clinical applications. We now demonstrate that only CCR7-and L-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
342
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 381 publications
(369 citation statements)
references
References 65 publications
23
342
4
Order By: Relevance
“…This happened although reproducibly more than 90% of the sorted cells expressed FOXP3 on the day of isolation ( [16] and H. and M. E. unpublished data). Possible explanations for the observed heterogeneity could be either contamination of the starting population with CD25 1 , non-regulatory Tconv that preferentially expand in culture over time, or, alternatively, the presence of a substantial number of ''converted'' or ''induced'' Treg that only transiently express FOXP3 after recent in vivo activation [22,23] and that re-convert to effector T cells during in vitro culture.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This happened although reproducibly more than 90% of the sorted cells expressed FOXP3 on the day of isolation ( [16] and H. and M. E. unpublished data). Possible explanations for the observed heterogeneity could be either contamination of the starting population with CD25 1 , non-regulatory Tconv that preferentially expand in culture over time, or, alternatively, the presence of a substantial number of ''converted'' or ''induced'' Treg that only transiently express FOXP3 after recent in vivo activation [22,23] and that re-convert to effector T cells during in vitro culture.…”
Section: Discussionmentioning
confidence: 92%
“…We previously showed that the heterogeneity in FOXP3 expression observed after prolonged in vitro expansion of bulk CD4 1 CD25 high T cells was predominantly caused by the emergence of FOXP3 À cells in the CD45RA À subfraction of the initial cell population [16]. Because at that time we had not included CD127 in our sorting strategy, we could not formally rule out contamination of the starting population with activated Tconv cells (which would be expected to reside primarily among CD45RA À memory cells).…”
Section: Epigenetic Changes In the Foxp3 Gene Locus Upon In Vitro Expmentioning
confidence: 99%
See 3 more Smart Citations